2005
DOI: 10.1161/01.cir.0000151517.43137.97
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Substrate of Atrial Fibrillation During Chronic Atrioventricular Block in the Goat

Abstract: Background-Atrial dilatation is an important risk factor for atrial fibrillation (AF). In the present study, we monitored the electrophysiological changes during progressive atrial dilatation in chronically instrumented goats. Methods and Results-In 8 goats, 2 screw-in leads with piezoelectric crystals were implanted transvenously in the right atrium. After 2 weeks, atrial diameter and effective refractory period were measured. AF paroxysms were induced by burst pacing to determine the baseline AF cycle length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
2
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 44 publications
6
71
2
3
Order By: Relevance
“…21 The relevance of these findings to postoperative and permanent AF in humans was assessed in samples of the RA appendage from 130 patients undergoing cardiac surgery (26 with permanent AF, 32 who developed AF postoperatively, and 72 in normal SR before and after surgery), as were the effects of ex vivo atorvastatin on NADPH oxidase-derived atrial ROS production, biopterin levels, and NOS activity.…”
Section: Clinical Perspective On P 1117mentioning
confidence: 99%
“…21 The relevance of these findings to postoperative and permanent AF in humans was assessed in samples of the RA appendage from 130 patients undergoing cardiac surgery (26 with permanent AF, 32 who developed AF postoperatively, and 72 in normal SR before and after surgery), as were the effects of ex vivo atorvastatin on NADPH oxidase-derived atrial ROS production, biopterin levels, and NOS activity.…”
Section: Clinical Perspective On P 1117mentioning
confidence: 99%
“…Chronic AVB and the resulting slow idioventricular rhythm in a goat can lead to progressive atrial dilatation. 29) Atrial dilatation is a predictor of recurrence of AF after catheter ablation. [23][24][25] However, because the slow idioventricular rhythm is prevented effectively by PM therapy in these patients, the effect of AVB on recurrence of AF need further studies.…”
Section: Discussionmentioning
confidence: 99%
“…40) Membrane currents activated by hypotonicity 41) or stretch 42) have been reported to be present on the cell membrane in the pulmonary vein cardiomyocytes, and to play important roles in their automaticity. In chronic atrioventricular block goat and dog models, 43,44) atrial dilatation induced by chronic volume overload was shown to produce a substrate of atrial fibrillation. In the chronic atrioventricular block dog, the action potential of the pulmonary vein myocardium became significantly shorter while that of the left atria did not.…”
Section: Effect Of Pathophysiological Status and Humoral Factorsmentioning
confidence: 99%